Strangers assume my girlfriend is my nurse - Burcaw, Shane (Roaring Brook Press, 2019)
"With his signature acerbic wit and hilarious voice, twenty-something author, blogger, and entrepreneur Shane Burcaw is back with an essay collection about living a full life in a body that many people perceive as a tragedy. From anecdotes about first introductions where people patted him on the head instead of shaking his hand, to stories of passersby mistaking his able-bodied girlfriend for a nurse, Shane tackles awkward situations and assumptions with humor and grace. On the surface, these essays are about day-to-day life as a wheelchair user with a degenerative disease, but they are actually about family, love, and coming of age."--